Empirical Analysis of Ethics Integration and Online Learning in Auditing Course on Ethical Decision Making: Further Evidence from Indonesia - Suryaningrum, Diah Hari; Subroto, Bambang; Sutrisno; Rahman, Aulia Fuad (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
Whether ethics should be taught and how it should be taught has been questioned by accounting professionals, researchers, and teachers. This experimental study attempts to answer the question and gives further evidence of the beneficial impact of teaching ethics. Participants are sixty students of professional accounting program in the first semester. Ethical decision making was measured using multidimensional ethical scale (MES) that has been used to measure attitudes related to justice, relativism, egoism, contractualism, and utility. MES also allows participants to provide explanation for their moral orientation in making decision. We also construct a ratio scale of participants’ confidence to measure ethical decision making. The scales are from 10 to 100 percent to answer question whether they believe that decision made was an ethical decision. Using 2x2 factorial experimentaldesign and analysis of variance, this study proved that interaction of ethics integration and learning method of online technology has positive impact on participants’ moral orientation. On the contrary, participants’ confidence level in making ethical decision is not related to ethics integration, but influenced by ethics integration and learning methods. These results indicate that ethics teaching can influence character and ability of participants’ moral orientation, but when making ethical decision, their confidence level in making ethical decision depend on circumstances faced.